DNA barcoding of grasshoppers (Orthoptera: Acridoidea) from the Bashang Grassland of Hebei, China - Li, Jing-Zhu; Chen, Jian-Yu; Yang, Jia-Tong; Zhao, Li-Ying; Guo, Jing; Li, Xin-Jiang (Zootaxa, 2025)
Grasshoppers are significant pests in agriculture, animal husbandry, and forestry. They are widely distributed and numerous species, with some taxa exhibiting considerable morphological variation, which poses substantial challenges for traditional taxonomic classification. DNA barcoding has become an essential tool for species identification, serving as an effective complement to morphological taxonomy. This study focuses on grasshoppers from the Bashang Grassland in Hebei Province, China. Mitochondrial cytochrome c oxidase subunit I (COI) gene sequences were used as DNA barcode sequences, which were obtained and analyzed using molecular biology techniques. In addition, homologous sequences of related species were retrieved from GenBank, resulting in a barcode dataset comprising 237 sequences from 42 species, 26 genera. Phylogenetic analysis barcoding gap assessment were performed, and multiple species delimitation methods—including ABGD, ASAP, GMYC, and mPTP—were applied for comprehensive evaluation. The results demonstrated that DNA barcoding can effectively delineate species-level taxonomic units for many grasshoppers, providing a powerful supplement to morphological taxonomy. However, the grasshopper taxa include both groups with high cryptic genetic diversity and closely related species that are difficult to distinguish using barcoding alone. Therefore, accurate identification of grasshopper species still requires integration with morphological approaches.